Digital Workplace – Advantages and Challenges - Rakovic, Lazar; Sakal, Marton; Matkovic, Predrag (Anali Ekonomskog fakulteta u Subotici, 2022)
Digital transformation is performed through the integration of information technologies into all areas of a business. The changes are radical, comprehensive and as such, they affect workplaces as well. Many authors overemphasize the use of technologies and regard them as central to the digital workplace. On the other hand, the position of the authors who argue that the digital workplace should coordinate technologies, processes and people is more correct. Theoretical research often does not clearly define the term digital workplace. Furthermore, the studies often overemphasize only the benefits while omitting the challenges presented by the digital workplace implementation. Therefore, the paper presents the requirements for a workplace to be considered digital, its advantages and challenges, and it shows how to balance the positive and negative repercussions of workplace digitalization.